2021
DOI: 10.1186/s12887-021-02550-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic outbreak on education and mental health of Chinese children aged 7–15 years: an online survey

Abstract: Background The emerging of psychological problems triggered by COVID-19 particularly in children have been extensively highlighted and emphasized, but original research in this respect is still lagging behind. Therefore, we designed this study to evaluate the impact of COVID-19 pandemic on mental health and the effectiveness and attitudes towards online education among Chinese children aged 7–15 years. Methods A detailed questionnaire, comprising o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
2
19

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(144 citation statements)
references
References 28 publications
10
102
2
19
Order By: Relevance
“…Under the pandemic context, there is little previous research about these educational experiences. These studies did not associate their findings with mental health, but we think it is important to highlight that they found a substantial proportion of students who are not comfortable or motivated by online education ( 19 , 20 ) and consequently, we can conclude that they may develop or increase mental health problems if we contrast this with our results, which is worrying.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Under the pandemic context, there is little previous research about these educational experiences. These studies did not associate their findings with mental health, but we think it is important to highlight that they found a substantial proportion of students who are not comfortable or motivated by online education ( 19 , 20 ) and consequently, we can conclude that they may develop or increase mental health problems if we contrast this with our results, which is worrying.…”
Section: Discussioncontrasting
confidence: 70%
“…Finally, in the context of the SARS-CoV-2 pandemic, some studies have found that educational factors have been negatively impacted by lockdown measures, especially the schools closing. For example, one study conducted in China reported that a substantial proportion of students were not comfortable or motivated by online education, and consequently, they did not participate effectively during the pandemic ( 19 ). Another study conducted in Italy and Portugal also found that online education was associated with lower students' motivation ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used Impact of Events Scale-Revised (IES-R) self-questioner to examine the psychological impact[ 6 , 7 ]. Further detail has been documented previously[ 5 ]. IES-R questioner was translated into Chinese language.…”
Section: Methodsmentioning
confidence: 99%
“…The teenagers were restricted at home for a long time and were the first to switch to online education. Although the rises of psychosomatic issues caused by COVID-19, especially in teenagers, have been widely reported [ 3 - 5 ], innovative investigation into this issue remains scarce. In this study, we conducted a large cohort survey in a high school at the end of the COVID-19 epidemic in China.…”
Section: Introductionmentioning
confidence: 99%
“…Strict guidelines with specific emphasis on protective measures such as city lockdowns, travel bans, and within-population quarantines were developed by the authorities for controlling the pandemic. As these measures lead to physical inactivity, they also had an adverse impact on health, such as promoting obesity, premature ageing, cardiovascular vulnerability, bone loss, muscle atrophy, decreased aerobic capacity[ 4 ], and psychological issues[ 5 - 8 ]. Physical activity is vital for public health[ 6 ], as it acts on the cardiovascular and respiratory systems[ 7 ].…”
Section: Introductionmentioning
confidence: 99%